Investigating the effects of Financial Accounting Reports on Managerial Decision Making in Small and Medium-sized Enterprises - et. al., Bayar Gardi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Financial accounting reports plays a major role in keeping track of all financial transactions. The management decision-making relies on accounting information, including the income statement, and cash flow statement reports recorded in corporate financial statements. Each financial statement for publicly traded companies shall be created and reported to the Securities and Exchange Commission following the financial accounting standards established by the Financial Accounting Standard Board. This current study examines the impacts of financial accounting reporting on management decision-making in small and medium-sized companies in Iraq. The study also investigates the management's attitude towards capital allocation to identify whether it maximizes the effectiveness of the decision. For this purpose, cross-sectional data analysis was used, and the data was collected from 250 respondents from managers and employees working in SMEs through a structured questionnaire. The study indicates the effectiveness of managerial decisions is substantially influenced by the financial statement report. The other operational considerations such as company records, understandability of reports, and quality of the data have a major impact on the managerial decision of the SME firms. The study identified understandability, relevance, and quality of the financial reports mediates a positive correlation between financial accounting reports and managerial decisions.